THEME: FRACTURES - Qo’ldosheva Mo’tabarxon Muhtarovna (TADQIQOTLAR.UZ, 2025)
What is a fracture? A fracture is a partial or complete break in the bone. When a fracture happens, it’s classified as either open or closed:  Open fracture (compound fracture): The bone pokes through the skin and can be seen. Or a deep wound exposes the bone through the skin.  Closed fracture (simple fracture). The bone is broken, but the skin is intact.